A randomised dose-ranging study of tiotropium Respimat® in children with symptomatic asthma despite inhaled corticosteroids. Issue 1 (December 2015) - Vogelberg, Christian; Moroni-Zentgraf, Petra; Leonaviciute-Klimantaviciene, Migle; Sigmund, Ralf; Hamelmann, Eckard; Engel, Michael; Szefler, Stanley
Abstract Background A considerable number of children with asthma remain symptomatic despite treatment with inhaled corticosteroids, resulting in significant morbidity, reduced quality of life, increased healthcare costs and lost school days. The aim of our study was to assess the efficacy, safety and tolerability of once-daily tiotropium Respimat® 5 μg, 2.5 μg and 1.25 μg add-on to medium-dose inhaled corticosteroids, with or without a leukotriene modifier, in children aged 6–11 years with symptomatic asthma. Methods In this Phase II, double-blind, placebo-controlled, incomplete-crossover, dose-ranging study, patients were randomised to receive three of the four treatments evaluated: once-daily tiotropium Respimat® 5 μg, 2.5 μg or 1.25 μg or placebo Respimat®, in the evening during the 12-week (three × 4-week) treatment period. Results In total, 76, 74, 75 and 76 patients aged 6–11 years received tiotropium Respimat® 5 μg, 2.5 μg, 1.25 μg and placebo Respimat®, respectively. For the primary end point (peak forced expiratory volume in 1 second measured within 3 hours post-dosing), the adjusted mean responses with tiotropium Respimat® 5 μg (272 mL), 2.5 μg (290 mL) and 1.25 μg (261 mL) were significantly greater than with placebo Respimat® (185 mL; p = 0.0002, p < 0.0001 and p = 0.0011, respectively). The safety and tolerability of all doses of tiotropium Respimat® were comparable with those of placebo Respimat®, with no serious adverse events and no events leading to discontinuation. Conclusions Tiotropium Respimat® add-on to medium-dose inhaled corticosteroids, with or without a leukotriene modifier, was efficacious in paediatric patients with symptomatic asthma and had comparable safety and tolerability with placebo Respimat®. Trial registration ClinicalTrials.gov identifierNCT01383499